Russian consensus statement on the diagnosis and treatment of patients with carotid stenosis - M. A. Chernyavsky; O. B. Irtyuga; S. N. Yanishevsky; A. S. Alieva; K. A. Samochernykh; K. B. Abramov; T. V. Vavilova; V. A. Lukyanchikov; D. I. Kurapeev; A. G. Vanyurkin; D. V. Chernova; N. K. Shelukhanov; et al. (Российский кардиологический журнал)
Carotid stenosis is a multidisciplinary problem that requires the involvement of a specialists’ team, including cardiovascular surgeons, neurosurgeons, endovascular surgeons, cardiologists, neurologists, and internists. In this consensus statement, a group of experts considered the main stages of diagnosing carotid stenosis, as well as discussed, the necessary prevention methods and features of choosing the optimal treatment approach. The aim was to provide concise and structured information on the management of patients with carotid stenosis. This document was developed based on the updated clinical guidelines of the European Society for Vascular Surgery and the American Association for Vascular Surgery, taking into account the consensus opinion of Russian experts.